Performance analysis on deposition of aluminium 6063 over en8 medium carbon steel by friction surfacing. (2022) - Sahoo, Dillip Kumar; Guna, P.; Deepan, S.
Abstract: The present study has attempted to produce a sound bonding of aluminium 6063 on EN8 carbon steel by adding inducting heating to the substrate plate in friction surfacing (FS). Substrate pre heating approach (SPHA) enhanced the rigorous plastic deformation of the consumable material, caused an increase the consumption rate of the coating material but the push off strength of the coating was increased as compared to the specimen received from classical approach (CA) which was due to the formation of steady dynamic recrystallization at coating interface. Development of coating mass and its influence on coating geometry were well presented by both approaches. Specimen obtained from SPHA of FS showed an increased joining and coating efficiencies by 10.6% and 5.8% respectively than CA approach of FS. Further, the mechanical strength of the coating was examined by bending and ram tensile testing that revealed a high bond strength of the specimen arrived from SPHA approach of FS. Microstructural attributes and interfacial characteristics of the coatings were explored by using high amplification FE-SEM image.